Novel β-TCP/PVA bilayered hydrogels with considerable physical and bio-functional properties for osteochondral repair. (7th December 2017) - Yao, Hang; Kang, Junpei; Li, Weichang; Liu, Jian; Xie, Renjian; Wang, Yingjun; Liu, Sa; Wang, Dong-An; Ren, Li
Abstract: Cartilage repairing grafts have been widely studied, and osteochondral replacement hydrogels have proven to be an excellent method in research and clinical fields. However, it has been difficult to simultaneously solve three main issues in osteochondral replacement preparation: surface lubrication, overall mechanical support and good simulations of cell regeneration. A novel integrated bilayered hydrogel osteochondral replacement was constructed by blending polyvinyl alcohol (PVA) and β -tricalcium phosphate ( β -TCP) in this study. Separated nano-ball milling with ultrasound dispersion prepared β -TCP demonstrated suitable properties of tiny particle size, high purity and ideal distribution, improving the mechanical properties of the novel integrated hydrogel, and providing a cartilage-like lubrication effect and high biocompatibility, including cytocompatibility and osteogenesis. The reinforcement of β -TCP and integrated molding technology enabled the hydrogel to demonstrate excellent component compatibility and good bonding between the two layers, which promoted the strengthening of the compression modulus and tensile modulus up to three times by mechanical testing. The surface lubrication properties of the novel osteochondral hydrogel were similar to the natural cartilage by friction coefficient characterization. The two layers of the novel integrated graft provided a considerable bio-function by co-culturing with chondrocytes and synovium mesenchymal stem cells: chondrocytes promoted adherence achieved by the upper density layer and better osteogenesis performance of the porous lower layer. The design of the bilayered β -TCP/PVA osteochondral hydrogel is promising for use in articular cartilage repair.